Dampak Gerakan Literasi terhadap Pemahaman Berbahasa di Kalangan Mahasiswa KPI Universitas Islam Bandung - Amelia Hanani; Rahmayana Rahmayana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the impact of literacy movements on language comprehension among students of the Islamic Communication and Broadcasting Program (KPI) at Universitas Islam Bandung. Using a qualitative approach with a descriptive design, the research explores the implementation of literacy movements, their influence on reading, writing, and speaking skills, as well as challenges faced by students. The findings show that literacy movements significantly enhance students’ language comprehension, both in academic and da’wah contexts. Identified challenges include low motivation, limited time, and inadequate supporting facilities. Proposed solutions include integrating literacy into courses, developing facilities, and implementing digital literacy programs. These findings are expected to serve as a reference for strengthening literacy movements in higher education.